Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE from an infectious complaint should be sent away to be disinfected, with the thick bedding. DON'T NEGLECT TORN GARMENTS Every article to be washed should be inspected when sorted out. The edges of rents and holes should be drawn together with coloured cotton to prevent further tearing until they can be mended. Stains and every soiled part should be noted. Always remove stains before washing, as soap and boiling water render certain stains fast dyes. (Methods of dealing with stains are given on pp. 25, 26 and 27.) NOW FOR THE WASH Wash the less soiled white articles first and then the dirtier ones. (The washing of fine muslins, silks, woollens and coloured garments is dealt with on pp. 27, 28 and 29.) The soiled parts may be soaped and rubbed between the fingers, or material may be rubbed against material if the latter is coarse. The articles may then be transferred to the wash-boiler, into which has been placed a suitable quantity of water and enough of a good washing preparation to give rich suds. The wash-boiler should then be gradually brought to the boil, after which boiling should be continued for two or three minutes, or for the period stated upon the soap powder packet. Very heavily soiled articles may require rather longer boiling. Fine linen, dress shirts and collars are best placed together in a pillow case, and care should be taken that they are put in the boiler before the water boils, as it is the gradual bringing to the boil which removes stains and loosens dirt. Page Twenty-two 177/5/8/1